Arthropod communities in fungal fruitbodies are weakly structured by climate and biogeography across European beech forests. Issue 5 (14th January 2019) - Friess, Nicolas; Müller, Jörg C.; Aramendi, Pablo; Bässler, Claus; Brändle, Martin; Bouget, Christophe; Brin, Antoine; Bussler, Heinz; Georgiev, Kostadin B.; Gil, Radosław; Gossner, Martin M.; Heilmann‐Clausen, Jacob; et al.
Abstract: Aim: The tinder fungus Fomes fomentarius is a pivotal wood decomposer in European beech Fagus sylvatica forests. The fungus, however, has regionally declined due to centuries of logging. To unravel biogeographical drivers of arthropod communities associated with this fungus, we investigated how space, climate and habitat amount structure alpha and beta diversity of arthropod communities in fruitbodies of F. fomentarius . Location: Temperate zone of Europe. Taxon: Arthropods. Methods: We reared arthropods from fruitbodies sampled from 61 sites throughout the range of European beech and identified 13 orders taxonomically or by metabarcoding. We estimated the total number of species occurring in fruitbodies of F. fomentarius in European beech forests using the Chao2 estimator and determined the relative importance of space, climate and habitat amount by hierarchical partitioning for alpha diversity and generalized dissimilarity models for beta diversity. A subset of fungi samples was sequenced for identification of the fungus' genetic structure. Results: The total number of arthropod species occurring in fruitbodies of F. fomentarius across European beech forests was estimated to be 600. Alpha diversity increased with increasing fruitbody biomass; it decreased with increasing longitude, temperature and latitude. Beta diversity was mainly composed by turnover. Patterns of beta diversity were only weakly linked to space and the overall explanatory power was low. We could distinguish two genotypes of F. fomentarius, which showed no spatial structuring. Main conclusion: Fomes fomentarius hosts a large number of arthropods in European beech forests. The low biogeographical and climatic structure of the communities suggests that fruitbodies represent a habitat that offers similar conditions across large gradients of climate and space, but are characterized by high local variability in community composition and colonized by species with high dispersal ability. For European beech forests, retention of trees with F. fomentarius and promoting its recolonization where it had declined seems a promising conservation strategy.